The Art of Movement: Camera Techniques in Film Cek Toko Sebelah 2 (Architecture Image Studies, 2025)
This study investigates the application of film camera techniques within the framework of the film "The Next Store 2". This study examines how the film's camera techniques foster a distinctive and immersive viewing experience, emphasizing visual and narrative innovation. This study employs a qualitative approach to analyze diverse camera approaches, including framing, composition, camera movement, and the application of atypical lenses. The findings indicate that the application of these camera methods not only improves the film's visual appeal but also deepens the narrative and emotional impact on the audience. This study examines the obstacles and opportunities encountered by filmmakers in employing experimental camera techniques, along with the impact of these approaches on the audience's perception and interpretation of the narrative. This study offers significant insights for filmmakers, critics, and researchers focused on the evolution of camera methods in contemporary cinema.